Perbedaan Efektivitas Video dan Flipbook Aktivitas Fisik Terhadap Pengetahuan Mahasiswa Kesehatan Masyarakat Universitas Sumatera Utara - Setiawati, Dian; Andayani, Lita Sri (UI Scholars Hub, 2022)
Bakground. Physical activity is one of the important points of the Presidential Instruction of the Republic of Indonesia Number 1 of 2017 regarding a movement that supports a healthy lifestyle in the community, namely Gerakan Masyarakat Sehat (GERMAS). USU's FKM students have a high level of light physical activity, which is 81.2%. One of the things that influenced him was that USU's FKM students rarely read information about physical activity. Aim. This study aims to determine the differences in the effectiveness of videos and flipbooks about physical activity on the knowledge of USU FKM students. Method. The research design used was a Quasi Experiment Design research design and a Non-Equivalent Control Group Design research design. Result. This study found that there were differences in the mean values of knowledge in the video and flipbook media groups. Whether or not the dependency value of the two variables is